HUBUNGAN MANUSIAWI MANAJEMEN PENDIDIKAN DALAM KAJIAN PERILAKU ORGANISASI - Muhammad Anggung Manumanoso Prasetyo (PENCERAHAN, 2022)
The study's goal is to describe qualitatively the reality of organizational development through the improvement of organizational behavior and human relations. Humane relationships with organizational and management environments were the focus of research discussions, as were qualitative paradigm with library research technique. Data is analyzed using research findings and the perspectives of educational management perspective. According to the findings of this study, competence in humane relationships plays a critical role in the effective organization of educational management. Humane relationships are characterized by ethical values, sympathy, and empathy attitudes. In a review of human relationship management, the educational environment and aspects of leadership are discussed. Leading as a problem solver possesses humane relationship skills that benefit its subordinates in resolving member problems. Individual positive behaviors can be created more effectively with both directive and non-directive guidance. An inclusive emotional approach can also increase the effectiveness of educational guidance in creating individual positive behaviors. In terms of institutional aspects, schools as organizations go through lifecycles that include stages of growth, development, and maturity.